2020
DOI: 10.1101/2020.12.03.20243592
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surgery & COVID-19: A rapid scoping review of the impact of COVID-19 on surgical services during public health emergencies

Abstract: BackgroundHealthcare systems globally have been challenged by the COVID-19 pandemic, necessitating the reorganization of surgical services to free capacity within healthcare systems.ObjectivesTo understand how surgical services have been reorganized during and following public health emergencies, and the consequences of these changes for patients, healthcare providers and healthcare systems.MethodsThis rapid scoping review searched academic databases and grey literature sources to identify studies examining su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A review of reorganization of surgical services during public health emergencies identified downstream consequences of delaying surgery, such as alterations in medical training. 31 Additional research is needed to explore other potential effects of delaying nonurgent surgeries on health care systems, such as intensity of resource use while patients are waiting for surgery (e.g., emergency department visits and hospital stays requiring intensive care stay). Mitigating the backlog of surgeries due to the response to COVID-19 by managing surgical waitlists and transforming surgical care is another important area of work to deal with the delayed surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…A review of reorganization of surgical services during public health emergencies identified downstream consequences of delaying surgery, such as alterations in medical training. 31 Additional research is needed to explore other potential effects of delaying nonurgent surgeries on health care systems, such as intensity of resource use while patients are waiting for surgery (e.g., emergency department visits and hospital stays requiring intensive care stay). Mitigating the backlog of surgeries due to the response to COVID-19 by managing surgical waitlists and transforming surgical care is another important area of work to deal with the delayed surgeries.…”
Section: Discussionmentioning
confidence: 99%